Survey Ability Futsal Shooting Accuracy of Ramayana Futsal Athletes - Handayani, Pipi; Handayani, Widya; Putri, Siti Ayu Risma (PPSDP International Journal of Education, 2024)
This study aims to assess the shooting accuracy of athletes at the Ramayana Futsal Club using quantitative descriptive research methods combined with survey techniques. The study focused on a total population of 25 athletes who participated in training sessions at the club. A total sampling approach was employed, meaning all 25 athletes were included in the study sample to ensure comprehensive data collection and analysis. The primary objective was to evaluate the shooting accuracy levels among these athletes and categorize their performance. The results of the research revealed that a significant portion of the athletes demonstrated vital shooting accuracy. Specifically, 40% of the participants achieved shooting accuracy within the outstanding category, indicating a high level of proficiency. Another 48% of the athletes fell into the excellent category, reflecting a solid but slightly less optimal shooting performance. However, 12% of the athletes were categorized as having poor shooting accuracy, suggesting areas that need improvement. From these findings, it can be concluded that while the overall shooting accuracy of the Ramayana Futsal athletes is generally good, there is room for improvement. The results highlight the need for a thorough analysis of shooting accuracy factors and suggest that a specialized training model should be developed. Such a model would aim to address the specific deficiencies and enhance the shooting skills of athletes, thereby improving their overall performance on the field.